Identification of the Grindulu Fault in Pacitan, East Java using Magnetic Method - Latifatul Cholifah; Nurul Mufidah; Eden Lazuardi; Bagus Jaya Santosa; Sungkono Sungkono; Arif Haryono (Universitas Negeri Surabaya, 2020)
Magnetic method in geophysical surveys is common for its non-destructive use of sub-surface structure delineation. In this study, ground-based measurements of magnetic intensity were performed using a set of instruments in some regions of Pacitan, a city in the southern area of East Java province. Based on these measurements, data acquisition was used to identify the Grindulu faulting zone in the region of interest, potentially vulnerable to geohazards. The data were first corrected using the IGRF and diurnal corrections. A filtering technique of upward continuation at a height of 900 m was then applied to separate local anomalies from regional ones as the targeted sources in the present case. These separate anomalies and their corresponding reductions to the poles as further filtering processes were analyzed for predicting the location and direction of the fault. The results, extracted from data analysis and interpretation, show that the main path of the Grindulu is directed along the NE-SW fault line or N60oE. The resulting anomalies also reflect that the Grindulu is a normal fault with surrounding minor faults lying across the Grindulu, calling for increased awareness of vulnerability in the city to seismic threats.